1998
DOI: 10.1016/s0304-3959(97)00202-9
|View full text |Cite
|
Sign up to set email alerts
|

Pain progression, intensity and outcomes following tonsillectomy

Abstract: The objective of this study was to assess outcomes of pediatric day surgery tonsillectomy. A total of 129 children, aged 5-16 years, and their parents were recruited from three urban hospitals which provided pediatric day surgery. Children reported pain on a visual analogue scale (VAS) in day surgery and then daily at home for 7 days. Parents reported outcomes of surgery, including fluid intake, nausea, vomiting and sleep disturbances. They also recorded analgesic administration. Three main results related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
143
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 7 publications
14
143
1
4
Order By: Relevance
“…In fact, it has been documented that up to 60% of parents seek consultation with their family doctors after tonsillectomy because of postoperative complications and concerns, including pain severity and duration. 9,32 Therefore, pain contributes to increased health care costs by increasing the need for unscheduled postoperative medical visits.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been documented that up to 60% of parents seek consultation with their family doctors after tonsillectomy because of postoperative complications and concerns, including pain severity and duration. 9,32 Therefore, pain contributes to increased health care costs by increasing the need for unscheduled postoperative medical visits.…”
Section: Figurementioning
confidence: 99%
“…2 Indeed, researchers outside the United States suggested high levels of pain after tonsillectomy and adenoidectomy, as well as undertreatment of postoperative pain by parents. [3][4][5][6][7][8][9][10][11] The majority of those studies, however, had methodologic limitations such as small sample sizes, limited use of validated pain measures, and lack of a standardized approach to anesthesia and surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain following tonsillectomy can be severe and last up to seven days with substantial associated distress for children and parents. 7 Acetaminophen and NSAIDs are commonly co-prescribed for postoperative analgesia, and combination therapy would simplify this regime. The results of a recent qualitative systematic review of the evidence for combining acetaminophen and an NSAID for postoperative pain in adults showed that the combination provided superior analgesia to either drug alone.…”
Section: Résumémentioning
confidence: 99%
“…In posttonsillectomy term, especially adult patients usually suffer from severe pain during several days and the pain decreases step by step in following 4 days [3]. There are various analgesic medications for pain management, the spectrum of which varies from acetaminophen to narcotic analgesics.…”
Section: Introductionmentioning
confidence: 99%